Mitochondrial Carbonic Anhydrase VA Deficiency in Neonatal Hyperammonemic Encephalopathy: Case Report - Sequeira, S (2021)
Hyperammonemia can be a potentially fatal disorder, secondary to several different etiologies, most commonly urea cycle defects and organic acidurias. The deficiency of mitochondrial carbonic anhydrase VA, a recently recognized metabolic disorder, results from abnormalities in the CA5A gene. This gene plays an important role in ureagenesis and gluconeogenesis, resulting in a secondary deficiency of several carboxylases and presenting as neonatal hyperammonemic encephalopathy. We describe the case of an almost 5-year-old child who had neonatal encephalopathy secondary to hyperammonemia wherein carbonic anhydrase VA deficiency was identified in him. His growth and development are normal despite no diet or medication for several years. We report this case as fewer than 20 patients have been described in the literature.